Intraoperative Ketorolac Dose of 15 mg Versus the Standard 30 mg on Early Postoperative Pain After Spine Surgery: A Randomized, Blinded, Non-inferiority Trial. Issue 5 (October 2017) - Duttchen, K. M.; Lo, A.; Walker, A.; McLuckie, D.; De Guzman, C.; Roman-Smith, H.; Davis, M.
Abstract : (Abstracted from J Clin Anesth, 41:11–15, 2017) Opioids are used for acute postoperative pain management despite significant disadvantages (nausea, vomiting, ileus, urinary retention, excess sedation, and respiratory depression) associated with their use. Nonsedating nonopioid analgesic agents, such as nonsteroidal anti-inflammatory drugs, are a prospective alternative treatment for pain after surgery.